Use newtons second law where a force downward is negative and upward is positive.

Newtons second law is:

`F_(n e t)=sum_i F_i=m a`

Which just says the sum of the net force is equal to the sum of the individual forces thats equal to the mass times the acceleration.

Now...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Use newtons second law where a force downward is negative and upward is positive.

Newtons second law is:

`F_(n e t)=sum_i F_i=m a`

Which just says the sum of the net force is equal to the sum of the individual forces thats equal to the mass times the acceleration.

Now let `F_h` be the upward for due to the helicopter and `F_g` be due to gravity. Then we know:

`F_(n e t) =F_h-F_g=F_h-mg=ma`

Solve for a.

`(F_h-mg)/m=a`

Plug in the values and let the acceration for gravity g be 10 m/s/s.

`(25,000 N-2,000 kg *10 m/s^2)/(2,000 kg)=a`

`(25,000 N-2,000 kg *10 m/s^2)/(2,000 kg)=a`

`(25,000 N-20,000 N)/(2000 kg)=a`

`(5,000 N)/(2,000 kg)=a`

`5/3 (m/s^2) =a`

Therefore the acceleration of the helicopter is 5/3 meters per second per second upwards.

**Further Reading**